An Ayurvedic Approach to Manage PCOS- A Case Study - Chittora, Saloni; Meena, Narendra Kumar; Dixit, Mahesh (International Research Journal of Ayurveda & Yoga, 2022)
Background Polycystic ovary syndrome (PCOS) is a common endocrine disorder in women of reproductive age. PCOS is also a leading cause of infertility. It occurs 20- 30% more frequently in young people of childbearing age.According to Ayurveda, PCOS is related to Nastartava or Anartava. Nashtartava or Anartava is the main characteristic of Bandhya Yonivapada and Pushpgni Jatharini. The word Aartava is used in the Samhita in connection with menstrual blood, ovum, and ovarian hormones. PCOS is mainly due to Avrana of Vata and Kapha so Vatanulomak, Kapha Shaman, and Pitta Vardhan, Aamapachana, Artava Janana Chikitsa, are effective. Main observations: A 31 Years Old Female Patient, Housewife by Occupation. With Polycystic Ovarian Syndrome Was Arrived to OPD of Prasuti Tantra and Stri Rog for Ayurvedic Treatment. Chief Complaint Was Irregular Menses, Scanty Menses, Backache, Hair falls and Constipation in the last 4 Years. Physical Examination Revealed Pulse, Blood Pressure, Temperature Within Normal Limits. No History of Any Chronic Disease or Any Other Medical or Surgical History. Result: This patient was treated with ayurvedic formulations like Punarnava Mandoor, Panchkol Churna, Chaturbeej Churna, Panchtikt Ghrit Guggulu, Triphala Guggulu, Dashmool Kwath, Haridrakhand. Only traditional Ayurvedic medicines were used during the treatment. So, Patient’s condition was assessed through improvement in symptoms. Therefore, this study was conducted to evaluate one of the treatment regimens for polycystic ovarian syndrome (PCOS). Conclusion: The study reached the conclusion that ayurvedic treatment was significantly effective in the treatment of polycystic ovarian syndrome (PCOS).